Stable Isotope Constraints on Marine Productivity Across the Cretaceous-Paleogene Mass Extinction - Sepulveda, Julio; Alegret, Laia; Thomas, Ellen; Haddad, Emily; Cao, Changqun; Summons, Roger E. (Paleoceanography and Paleoclimatology, 2019)
The effects of the Cretaceous-Paleogene (K/Pg) mass extinction (similar to 66 Ma) on marine primary and export productivity remain debated. We studied changes in carbon and nitrogen cycling in eight neritic and upper bathyal sections with expanded K/Pg boundary clay layers in the western Tethys and northeastern Atlantic Ocean, by measuring stable carbon isotopes of bulk carbonate (delta C-13(carb)) and organic matter (delta C-13(org)), nitrogen isotopes in bulk organic matter (delta N-15), and selected compound-specific carbon isotopic records (delta C-13(lipid)). Negative carbon isotope excursions (CIEs) in delta C-13(carb), delta C-13(org,) and delta C-13(lipid) are temporally and spatially heterogeneous as well as decoupled from each other, suggesting that factors affecting the delta C-13 of dissolved inorganic carbon, as well as isotopic fractionation during carbon fixation across the K/Pg, are more complex than commonly assumed. The negative CIEs in delta C-13(org) and delta C-13(lipid) at each site are smaller in amplitude and shorter in duration than those in delta C-13(carb), but in most sections both carbon pools recovered to preboundary conditions within the time of deposition of the boundary clay layer (<10(3)-10(4) Kyr) or shortly thereafter. This rapid recovery is supported by limited delta N-15 data, which mostly suggests moderate or minor changes in redox conditions (except in Denmark), marine productivity, and phytoplanktonic nitrate utilization in the earliest Danian. Our results indicate that carbon cycling and primary productivity in neritic and upper bathyal regions recovered to preboundary levels faster (<10(4) Kyr) than in oceanic regions (10(5)-10(6) years), likely sustained by resilient noncalcifying phytoplankton with resting stages, consistent with modeling and proxy studies. Plain Language Summary Sixty-six million years ago, at the boundary between the Cretaceous and Paleogene Periods (K/Pg boundary), a meteorite impacted the Earth during a time of active volcanism causing the ...